THE IMPACT OF ARGUMENT-DRIVEN INQUIRY ON STUDENTS' CONCEPT MASTERY AND SUSTAINABILITY AWARENESS IN LEARNING GLOBAL WARMING - Erning Rahmadini Salsabila, - (2018)
The process of learning science in some schools is still in the form of direct transfer from teacher to student. The learning process will be meaningful if the students involved and explore more in building a concept. Argument-Driven Inquiry becomes one of alternative way to improve the participation of student during the learning process. The aim of this study is to investigate the impact of Argument-Driven Inquiry on students' concept mastery and sustainability awareness in learning global warming. The method that is used in this study is the mixed method with convergent parallel design. The population of this study is seventh-grade students in one of Junior High School in Bandung, Indonesia. The sample is chosen by purposive sampling technique. The participant was 52 students from experimental group and control group. Each group consist of 26 students. The result of this study shows the improvement of students' concept mastery in experimental group is obtained as 0.45 and for the control group is 0.28. It shows that the improvement of students' concept mastery which is using Argument-Driven Inquiry is better than the control group. The percentage of each aspect of sustainability awareness in experiment group is higher than control group. Based on the result, Argument-Driven Inquiry gives the better impact in improving students' concept mastery and sustainability awareness. It can be considered as one of the alternative of teaching models that can be implemented in Junior High School. Proses pembelajaran IPA di beberapa sekolah masih disampaikan secara langsung oleh guru kepada siswa. Proses pembelajaran akan lebih berarti jika siswa ikut terlibat dan bereksplorasi lebih banyak dalam membangun sebuah konsep. Argument-Driven Inquiry dapat menjadi salah satu cara alternatif untuk meningkatkan partisipasi siswa selama proses pembelajaran. Tujuan dari penelitian ini adalah untuk menyelidiki pengaruh dari Argument-Driven Inquiry terhadap penguasaan konsep dan sustainability awareness siswa dalam pembelajaran pemanasan global. Metode yang digunakan dalam penelitian ini adalah mixed method dengan desain paralel konvergen. Populasi pada penelitian ini adalah siswa kelas 7 dari salah satu SMP yang berlokasi di Bandung, Indonesia. Sampel dipilih dengan teknik purposif. Sampel yang digunakan berjumlah 52 siswa dari kelas eksperimen dan kelas kontrol. Masing-masing kelas terdiri dari 26 siswa. Hasil dari penelitian ini adalah peningkatan penguasaan konsep siswa pada kelas eksperimen diperoleh N-gain sebesar 0,45 dan pada kelas kontrol sebesar 0,28. Hal tersebut menunjukkan peningkatan penguasaan konsep siswa pada kelas eksperimen yang menggunakan Argument-Driven Inquiry lebih baik dari kelas kontrol. Persentase dari setiap aspek sustainability awareness pada kelas eksperimen juga lebih tinggi dari kelas kontrol. Berdasarkan hasil tersebut, Argument-Driven Inquiry memberikan pengaruh yang lebih baik terhadap peningkatan penguasaan konsep dan sustainability awareness siswa. Argument-Driven Inquiry dapat dijadikan sebagai salah satu alternatif model pembelajaran yang dapat di implementasikan di SMP.